2016
DOI: 10.1182/blood.v128.22.5653.5653
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Phenotype Profile Related to the Extramedullary Involvement in Multiple Myeloma Relapse

Abstract: Background: Multiple myeloma (MM) is characterised by proliferation of malignant plasma cells (PCs) usually in bone marrow (BM). The mechanisms of extramedullary (EM) spread in MM are poorly understood. It probably involves possible changes in expression of adhesive molecules. An increase incidence of aggressive and mostly resistant EM relapses was reported in the era of new treatment approaches. Finding a marker allowing predict a risk of EM relapse could help to improve treatment strategies and prolong patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The current data did not find that the incidence of 17p deletion, 1q amplification, and chromosome 14 translocation increased in EMM. Furthermore, EMM has different characteristics from MM at the molecular level, which is mainly involved in the downregulation of cell adhesion and chemokines, while the upregulation of cell migration, proliferation, and immune escape ( 2 , 23 , 24 ). In addition, the gene expression profiles showed that EMM had high-risk characteristics, such as the proportion of MF subtype and PR subtype, which were significantly higher than those of patients without EM ( 12 , 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current data did not find that the incidence of 17p deletion, 1q amplification, and chromosome 14 translocation increased in EMM. Furthermore, EMM has different characteristics from MM at the molecular level, which is mainly involved in the downregulation of cell adhesion and chemokines, while the upregulation of cell migration, proliferation, and immune escape ( 2 , 23 , 24 ). In addition, the gene expression profiles showed that EMM had high-risk characteristics, such as the proportion of MF subtype and PR subtype, which were significantly higher than those of patients without EM ( 12 , 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…High nestin levels in MM patients were strongly associated with the presence of 1q21 gain and seemed to be a predictor of worse response to therapy; its higher expression was observed in disease progression 49,50 . Increased nestin expression was also found in MM with extramedullary involvement 37 . Nestin was described only on a limited number of PCLs with a low level of expression in pPCL 50 .…”
Section: Discussionmentioning
confidence: 98%
“…20 As our group published previously, expression of CD56 was also not changed in different MM cases (extramedullary vs. intramedullary relapses), so its loss probably should not be considered as a marker of extramedullary spread. 37 A larger decrease in expression of CD56 in PB than in BM is not easily explained. Rawstron et al revealed the same composite phenotype in paired samples of PB and BM in MM, with significantly lower expression of CD56 and CD138 in PB.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations